Public Health Midwives as a Family Health Care Worker to Promote Vaginal Health: Evidence from a Community Study in Sri Lanka - Ilankoon Mudiyanselage Prasanthi Sumudrika ILANKOON; Christine Sampatha Evangeline GOONEWARDENA; Rukshan Cleophas FERNANDOPULLE; Poruthotage Pradeep Rasika PERERA (Tehran University of Medical Sciences, 2020)
No Abstract